SISTEM JADWAL PEMAKAIAN LABORATORIUM KOMPUTER PADA UNIVERSITAS MUHAMMADIYAH JAMBI - Marthiawati, Noneng; Kurniawansyah, Kevin; AR, Hetty Rohayani. (LPPM Universitas Muhammadiyah Jambi, 2022)
The laboratory is an academic support unit in an educational institution, in the form of a closed or open room that is permanent, managed systematically for teaching and learning activities, research, experiments as well as for practical and learning activities both individually and in groups. The laboratory at the Muhammadiyah University of Jambi has limited capacity, equipment and numbers because it is not proportional to the number of students, so students cannot master this value. These limitations can be overcome by scheduling the use of space. The current schedule for computer laboratory practicum can only be seen on the paper attached to the laboratory room and for the process of borrowing the laboratory, lecturers and students must come directly to the laboratory to communicate the laboratory loan to the head of the computer laboratory to see if there is an empty schedule. From the problems above, the purpose of this study is to design a Laboratory Usage Schedule System to make it easier for lecturers and students, especially the head of the laboratory, to access laboratory usage schedules regarding borrowing empty laboratories and substitutes for learning with the prototyping system method which results in increasing the effectiveness and efficiency of implementation to overcome existing problems